BIOCHEMICAL FEATURES OF POSTOPERATIVE SKIN WOUNDS HEALING AGAINST THE BACKGROUND OF DIABETES MELLITUS IN RATS WITH DIFFERENT WAYS OF WOUND CLOSURE - Loza, Ye.O.; Marushchak, M.I.; Denefil, O.V.; Avetikov, D.S.; Kulyanda, О.О. (World of Medicine and Biology, 2020)
The study is devoted to identifying the features of free radical processes changes in skin homogenate of the rats with diabetes mellitus, after using different methods of surgical wounds closing. Analysis of the results suggests that the use of skin glue significantly reduces the intensity of the free radical oxidation course in the cells of scarred skin tissues in animals with simulated diabetes mellitus compared to the application of nodal sutures to the wound under similar conditions.
Keywords: free radical oxidation; oxidative stress; abnormal scar